2019
DOI: 10.1038/s41467-019-13600-9
|View full text |Cite
|
Sign up to set email alerts
|

SAM-VI riboswitch structure and signature for ligand discrimination

Abstract: Riboswitches are metabolite-sensing, conserved domains located in non-coding regions of mRNA that are central to regulation of gene expression. Here we report the first three-dimensional structure of the recently discovered S-adenosyl-L-methionine responsive SAM-VI riboswitch. SAM-VI adopts a unique fold and ligand pocket that are distinct from all other known SAM riboswitch classes. The ligand binds to the junctional region with its adenine tightly intercalated and Hoogsteen base-paired. Furthermore, we revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
5
21
0
Order By: Relevance
“…The bound adenosine moiety becomes an integral part of the helix, at the interface between the extended P1 and the PK helices. A similar manner of SAM binding was observed in the recent structure of the SAM-VI riboswitch ( 23 ) ( Supplementary Figure S6D ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The bound adenosine moiety becomes an integral part of the helix, at the interface between the extended P1 and the PK helices. A similar manner of SAM binding was observed in the recent structure of the SAM-VI riboswitch ( 23 ) ( Supplementary Figure S6D ).…”
Section: Discussionsupporting
confidence: 80%
“…Lastly, the SAM-III riboswitch ( 21 ) uses a three-way helical junction to create the SAM binding site; ( 22 ). The SAM-VI riboswitch has been classed within the SAM-III family ( 11 ), although a recent structural study suggests that this riboswitch should be classified on its own ( 23 ). In addition to these riboswitches, a SAH-binding riboswitch has also been identified ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…For fluorescent labeling by non-covalent interactions, we refer the reader to recent reviews in this field. 7,25,52,53 Covalent labeling of nucleic acids has become the gold standard for numerous biophysical studies, such as elucidation of structure and dynamics of different functional nucleic acids, 54,55 probing of local viscosity, 56 optical genome mapping, 57 or electro-optical nanopore sensing. 58 In general, a covalent fluorescent label can either be introduced directly into the nucleic acid of interest, or in a two-step approach, meaning that first a reactive handle is installed that allows for subsequent post-synthetic functionalization using the above mentioned click reactions.…”
Section: Fluorescent Labeling Of Nucleic Acidsmentioning
confidence: 99%
“…77 Excitation of 2-aminopurine is selective, due to a red-shifted absorption from 260 nm to 303 nm in an aqueous solution at neutral pH. 78 The 2-aminopurine nucleoside was extensively used for elucidation of structure and dynamics of different functional nucleic acids, like the SAM-IV riboswitch 54 or the hammerhead ribozyme. 55 However, several studies revealed that the fluorescence of 2-aminopurine is highly susceptible to several parameters: the pH, 78 the polarity of the solvent, the concentration of nucleotides in solution 77 and the stacking of 2-aminopurine with purines and thymidines 79 -these affected the excitation and emission wavelengths, the fluorescence lifetimes and the quantum yield.…”
Section: Fluorescent Labeling Of Nucleic Acidsmentioning
confidence: 99%
“…111 The SAM-VI riboswitch adopts a new fold that recognizes its ligand in a distinct manner compared to the previously known five SAM riboswitch classes. 112 Tetrahydrofolate riboswitches. The folE motif RNAs selectively interact with the ubiquitous cofactor tetrahydrofolate (THF) and are commonly found in Gram-negative bacteria.…”
Section: Riboswitch Rnasmentioning
confidence: 99%